Finite element analysis of internal penny-shaped crack problem in an unbounded thermoelastic medium. Issue 10 (2nd October 2016) - Abbas, Ibrahim A.
ABSTRACT: In this article, the generalized thermoelastic theory with one relaxation time is used to investigate the internal penny-shaped crack problem in an unbounded thermoelastic material. The boundary of the crack is subjected to a prescribed stress distribution and temperature. The problem has been solved numerically using a finite element method. The results of the temperature, displacement components, and stress components have been verified numerically and are represented graphically. Comparisons are made with the results predicted by the presence and absence of the relaxation times.